(3VeGfGJ GdeJge ai eQMdI GdeMGceI GdLfGFjI (B: s (3OQGSI JMdjdjI JGUjdjI ebGQfI (B/ s - (3eMeO HgGA GdOjf GHhTbIs; (3MSfjf GHQGgje UGdM YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3jYJHQ GdHMK ai VeGfGJ GdeJge ai eQMdI GdeMGceI ef ehVhYGJ bGfhf GdGLQGAGJ GdLfGFjI (B: (3GdG Gf LhGfHg JQJHW HGaQY GNQi ef GdbhGfjf (B: (3cbGfhf GdSdWI GdbVGFjI (B: (3hGdeQGaYGJ (B: (3aVdG Yf Gf GdYOjO ef Jdc GdVeGfGJ JLO dgG GSGSG OSJhQjG (B: (3hgh eG jYfi hLhH GdHMK ai QHhY Jdc GdGaQY GdeNJdaI (B: (3hGdGdeGe HgG HGdbOQ GddGRe dGSJLdGA Jdc GdVeGfGJ (B: (3hJGUjdgGhbO TZdJ acQI VeGfGJ GdeJge ai eQMdI GdeMGceI MjRG cHjQG Ydi GdUYjO GdbGfhfi GdhWfi hGdOhdi (B: (3hgh eG JcQS ai fUhU GdOSGJjQ hGdJTQjYGJ (B: (3aVdG Yf GdGJaGbjGJ hGdehGKjb GdOhdjI GdeYfjI HMbhb GdGfSGf (B: (3Pdc Gf GdeJge GfSGf (B: (3jJeJY HbQjfI GdHQGAI GdJi dG Jfac Yfg deLQO GJgGeg (B: (3aGPG eG bGe ehLH dgPG GdGJgGe (B: (3cGf ef GdeJYjf Gf jbGHdg JbQjQ VeGfGJ Jcad dg Mbg ai eMGceI YGOdI efUaIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3HHdjhLQGajG(B: (3UaMGJ (B464-488s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI ZSd GdGehGds; (3GdGKGQ GdGbJUGOjI dYedjGJ ZSd GdGehGds; (3GQcGf LQjeI ZSd GdGehGds; (3YbhHGJ LQjeI ZSd GdGehGds; (3GdehGLgI GdLfGFjI dLQjeI ZSd GdGehGds; (3GdJYGhf GdOhdj GdGLQGFj aj ecGaMI ZSd GdGehGds; (3GdGJaGbjGJ GdOhdjI aj eLGd ecGaMI ZSd GdGehGds; (3PGJjI GdGLQGAGJ GdLfGFjI aj LQjeI ZSd GdGehGds; (3GdeUdMI eMd GdMeGjI GdLfGFjI aj LQjeI ZSd GdGehGds; (3JSdje GdeLQejf aj LQjeI ZSd GdGehGds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs